Silent Battle Cries: Exploring the Lived Experiences of Nurses’ Working Condition - Rosario, Wilbert O (ASEAN Multidisciplinary Research Journal, 2021)
Nursing is widely regarded as a noble profession in the society that promotes the practice of caring of life (Kevin, 2014). Being a nurse in today’s chaotic healthcare environment is a very complex challenge. With the required formal knowledge and skills in patient care, nurse performs a complex role among the multidisciplinary team. According to Bavier (2018), nurses have a vital role in the health care delivery process, along with their “varying roles as dependable counselors, comforters, confidants and great listeners”. This study aimed to explore the lived experiences of nurses’ work condition in Pangasinan. This qualitative research utilized phenomenology as its research design. They were chosen through purposive sampling, and data were gathered through a semi-structured interview. The data gathered were analyzed based on Colaizzi (1978) method. The data were transcribed, clustered and analyzed carefully. The findings illustrate themes and subthemes include: Lived Experiences, subthemes: Physical Exhaustion, Emotional Distress, Social Stagnation, and Detrimental to Memory Function. Florence Nightingales’ Battle Cries, subthemes: Under-remuneration and Underemployment, Inadequate Resources, Limited appreciation and Misaligned of Nursing Role. The Atmosphere in Discerning Quality Care Service, subthemes: Providing and Promoting Quality Health Care Services, and Preventing Illnesses. The study concluded distinct similarities were marked based on their experiences that can affect person as holistic. Therefore, researcher recommend Philippine Nurses Association to determine which factors influence productivity of nursing staff and eventually ignite the voice to appeal for what is just and fair to the nurses.